Implementation of Patient Safety Culture Survey in Jombang Islamic Hospital - Lathifah, R; Ramadhan, N A; Jibril Al Farabi, M; Chalidyanto, D (KnE Life Sciences, 2018)
Patient safety is the indicator of healthcare service quality. To improve patient-safety culture in hospital, conducting a survey is important to determine which dimension should be managed. Jombang Islamic Hospital (Rumah Sakit Islam Jombang) has an established Patient Safety Team since 2011, but the patient-safety culture is still low because only three incidents were reported in 2015. This study aims to measure patient-safety culture in hospital to identify the factors that need to be improved in hospital unit. This was a descriptive analytic study. Primary data were collected in 2016 using an Indonesian-translated version of Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. The HSOPSC measures 12 patient safety dimensions. The respondents were 117 Jombang Islamic Hospital staff members who work in hospital unit that gives a direct medical service. Questionnaire's final response rate was 91%. The overall average positive response in Jombang Islamic Hospital was 68%, slightly higher than the average positive response for the AHRQ database report in 2016 (65%). Pharmacy had the lowest positive response (54%), while Obstetric and Operation Room had the highest positive response (83%). The dimension that received the highest percentage of positive response was ‘Teamwork within units’ that reached 94% and the lowest was ‘Staffing’ with only 34%. This study concludes that the staff members feel positive toward patient-safety culture. It is important to give an intervention to hospital unit and dimensions that received low percentage of positive response in order to achieve better healthcare service quality. Keywords: HSOPSC, hospital dimension, patient safety culture, survey